Patogenesis Melasma - Diahtantri, Riyantia Astrid; Menaldi, Sri Linuwih; Mughni, Fadhli Aulia (PT Kalbe Farma Tbk., 2024)
Melasma is a chronic skin pigmentation disorder caused by sunlight exposure. Melasma is a multifactorial disease with various pathways that can induce hyperpigmentation. Exposure to ultraviolet (UV) light as a source of reactive oxygen species (ROS) and free radicals plays a role in the pathogenesis of melasma. Another mechanism is the role of ROS on melanogenesis and melanocyte cells as well as the signaling pathway for melanin synthesis. Concentration of antioxidants as a skin defense against ROS, namely superoxide dismutase (SOD), catalase, and glutathione peroxidase, also influences the occurrence of melasma.